2013
DOI: 10.1177/0025802412473594
|View full text |Cite
|
Sign up to set email alerts
|

Microbial ethanol production in postmortem urine sample

Abstract: We present a case in which postmortem blood ethanol concentration was 0.02 g/kg and acetone concentration was 0.51 g/kg, while urine ethanol concentration was 6.0 g/kg and acetone concentration was 0.63 g/kg. In the urine sample, sodium fluoride was not added. The urinary ethanol concentration continued to increase without any remarkable increase of isopropanol concentration and external contamination was excluded. Species of bacteria and yeasts, including Candida glabrata, were isolated from urine and blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Several studies have shown apparent postmortem increases in ethanol concentration in the blood and urine of diabetics with high blood or urine glucose concentrations, or in persons who have received intravenous glucose, due to microbes and especially if fungus such as Candida is present (1316). Such authors point out the need to preserve urine with sodium fluoride as is done with blood.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown apparent postmortem increases in ethanol concentration in the blood and urine of diabetics with high blood or urine glucose concentrations, or in persons who have received intravenous glucose, due to microbes and especially if fungus such as Candida is present (1316). Such authors point out the need to preserve urine with sodium fluoride as is done with blood.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, presence of fluoride ions in the blood inhibits the in vitro neoformation of ethanol [5,6]. However, case reports indicate possible in vitro formation of ethanol in spite of addition of fluoride [32,33].…”
Section: Occurrence Of Neoformation Of Volatiles In Human Remains Foumentioning
confidence: 99%